Designer case studies [videorecording] architecture, crafts and industrial design. (VEA, 2011)
Broken into three distinct section - Architectural Design, Craft Design, and Industrial Design - this video explores the work of different designers, namely Aaron Wallis, Wade Trevaen, Steve Baker and Alicia Mintzes.